Enhancing Students' Pronunciation By Using The Spotify App: English - Nurinda Permata Sari; Rahmah, Zaidatur; Rouhan Xu; Talitha Zafirah (JELT : Journal of English Education, Teaching and Literature, 2024)
English is very important because, in this increasingly advanced era, English is used as more assessment to fulfill a requirement such as work, exams in school, and many other things to increase self value. The researchers chose to use qualitative methods by distributing questionnaires that also leverage the advances in Google Form. The results of research obtained prove that the use of Spotify helps students improve pronunciation. The study concluded that Spotify helped improve pronunciation through hearing aspects and new vocabulary that is easily stored in memory because it is presented through music and lyrics that are easily accessible. Spotify deserves to be considered one of the learning media with easy use and fun so that the learning process continues to evolve with results that also look good to help improve pronunciation as one of its most important aspects in English-speaking communication.